The Implement’s Steganografi LSB dan Kriptografi AES-256 untuk Pengamanan Data Citra Digital - Muhammad Haris; Dedi Irawan; Gunawan Gunawan; Mahardika Abdi Prawira Tanjung (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Digital data security has become a critical issue in the digital transformation era, particularly in the exchange of digital images that are vulnerable to interception and manipulation by unauthorized parties. This study aims to implement a layered data security method by combining Advanced Encryption Standard (AES) 256-bit cryptography and Least Significant Bit (LSB) steganography on PNG-format digital images. The approach used is encrypt-then-embed, where the secret message is first encrypted using AES-256 in CBC mode, then the ciphertext is embedded into the cover image pixels through LSB bit substitution. Testing was conducted on five test images with varying resolutions (256×256 to 1024×768 pixels) using Peak Signal-to-Noise Ratio (PSNR), Mean Squared Error (MSE), entropy, avalanche effect, and computation time metrics. The test results show an average PSNR of 70,58 dB and MSE of 0.11, indicating excellent visual quality of the stego images. Security analysis shows an average avalanche effect of 50.29%, approaching the ideal value of 50%, and stego image entropy approaching 7.0545 bits/pixel. The computation time for encryption and embedding processes ranges from 0,005847 to 0,006078 seconds. The combination of AES-256 and LSB has proven effective in providing layered security: AES-256 ensures data confidentiality, while LSB conceals the message existence within the image without significant visual degradation.